Identification of CXCL12 as a key gene of trophoblast and endometrial stromal cell decidualization in pregnancy via scRNA-seq and experimental validation - Sun, Xianli; Yang, Haimei; Leng, Zhe; Zhang, Wei; Jiang, Zhou; Liu, Henglian (Frontiers in Molecular Biosciences, 2026)
BackgroundRecurrent miscarriage (RM) remains a significant clinical challenge due to its elusive pathogenesis. This study aimed to investigate the role of chemokine ligand 12 (CXCL12) at the maternal-fetal interface and its specific mechanism in RM, to provide an experimental basis for potential diagnostic and therapeutic strategies.MethodsWe utilized single-cell RNA-sequencing (scRNA-seq) to distinct single-cell atlas at the maternal fetal interface in normal and RM samples. And we comparably analyzed the expression of CXCL12 of Syncytiotrophoblast/Extravillous Trophoblast (SCT/EVET) in normal and unexplained RM pregnancies at the early stage of gestation. A CXCL12 silencing and overexpression system was established in the HTR-8/SVneo cell line. Cell viability was determined by MTT assay. The horizontal migration ability of HTR-8 cells was determined by cell scratch assay, while the invasion ability was tested by transwell matrix gel invasion assay. Recombinant human CXCL12 was used to stimulate endometrial stromal cells to explore the role of CXCL12 in the process of endometrial decidualization.ResultsSingle-cell atlas at the maternal fetal interface in normal and RM samples showed 11 cell types, including DSCs and SCT/EVT cells. In SCT/EVT cells, CXCL12 was remarkably decreased in RM cases. CXCL12 overexpression significantly promoted the proliferation, migration, and invasion ability of HTR-8 cells, while silencing CXCL12 significantly inhibited the proliferation, migration, and invasion ability of HTR-8 cells. Recombinant human CXCL12 significantly promoted the decidualization process of endometrial stromal cells, while decidualization was inhibited by CXCR4-neutralizing antibodies to a certain extent.ConclusionCXCL12 promotes the proliferation, migration, and invasion ability of trophoblast cells in vitro and promotes the decidualization of endometrial stromal cells. The downregulation of the CXCL12/CXCR4 axis may be involved in the occurrence and development of RM. Thus, this study provides experimental clues for exploring potential therapeutic approaches related to CXCL12.